2014
DOI: 10.1007/s11240-014-0562-9
|View full text |Cite
|
Sign up to set email alerts
|

Embryogenesis, plant regeneration and cardiac glycoside determination in Digitalis ferruginea subsp. ferruginea L

Abstract: The present study reports, for the first time, an efficient in vitro plant regeneration protocol for Digitalis ferruginea subsp. ferruginea L. (rusty foxglove). We have used different concentrations of gibberellic acid (GA 3 ) on Murashige and Skoog (MS) medium to assess the germination frequency of seeds. High frequency of germination was achieved on MS medium with 1.0 mg l -1 GA 3 . 6-Benzylaminopurine (BAP) combined with a-naphtaleneacetic acid (NAA) or 2, 4-dichlorophenoxy acetic acid (2, 4-D) in the induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 31 publications
3
7
1
Order By: Relevance
“…The results are in accordance with Hesami and Dhaneshvar [ 47 ], who found that 1.5 mg/L BAP along with 0.15 mg/L IBA showed 100% shoot regeneration frequency. Contrary to our observation, BAP with NAA was proved to be an efficient combination for indirect shoot regeneration in Digitalis ferruginea [ 37 ], Rauvolfia serpentina [ 48 ] and Aspilia africana [ 49 ].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The results are in accordance with Hesami and Dhaneshvar [ 47 ], who found that 1.5 mg/L BAP along with 0.15 mg/L IBA showed 100% shoot regeneration frequency. Contrary to our observation, BAP with NAA was proved to be an efficient combination for indirect shoot regeneration in Digitalis ferruginea [ 37 ], Rauvolfia serpentina [ 48 ] and Aspilia africana [ 49 ].…”
Section: Discussioncontrasting
confidence: 99%
“…Seed dormancy is a common problem encountered in various plant species that leads to delayed fruit set formation and reduced production of viable plants. GA 3 is widely known to break seed dormancy, and it has also been used in promoting the seed germination rate under in vitro conditions in other species of Digitalis , such as D. ferruginea [ 37 ] and D. cariensis [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, shoot regeneration was also achieved from embryogenic calli that was already cultured for somatic embryos (Data not shown; Table 2 ). However, shoot development on the callus was mediated via organogenic-like shoot meristems previously reported by Verma et al [51] . Therefore, it can not be ruled out that, next to somatic embryogenesis, adventitious shoot formation was also involved in the plant propagation [51] .…”
Section: Discussionmentioning
confidence: 69%
“…Digoxin and digitoxin were not detected in either source [69]. Efficient in vitro plant regeneration protocols for Digitalis ferruginea were also reported [70].…”
Section: Biology and Physiologymentioning
confidence: 99%